Nitrogen Dynamic in Agricultural Soils Amended With Sewage Sludge - de Melo, Wanderley J. [UNESP]; de Melo, Gabriel M.P.; de Melo, Valéria P.; Donha, Riviane M.A. [UNESP]; de Lima Dias Delarica, Denise [UNESP] (Elsevier, 2018)
The inappropriate use of natural resources has led to a decrease in environmental quality. Improper handling of waste can cause changes in the cycle of the elements in nature and generates greenhouse gases such as carbon dioxide, methane, and nitrous oxide. Agriculture has a great potential to enhance these changes due to the use of conventional soil management and the application of large amounts of mineral fertilizers. The excess of mineral N fertilizer can contaminate the environment with nitrate or contribute to global warming by a nitrous oxide emission. The use of conservation tillage systems such as direct drilling, crop rotation, and adequate disposal of organic wastes can help mitigate global warming by increasing the soil content of carbon and nitrogen. A study case is presented focusing on the use of sewage sludge (SS) in agriculture and its effect on soil nitrogen, nitrogen plant nutrition, crop production, and the protein concentration of the grains provided the following: (i) 5, 10, and 20Mgha1 of SS presented the same nutritional state in relation to N than the control receiving mineral fertilizers; (ii) there was leaching of NH4+ and NO3? to the 40-60cm layer; (iii) in high doses of SS the fraction of the N present in the soil surface that leached to the deeper layers was smaller; and (iv) organic fertilization with SS improved the protein concentration of corn grains.
Keywords: Ammonium; Nitrate; Organic waste; Plant nutrition; Soil properties